Komitmen Abu Bakar dalam Peristiwa Hijrah Nabi Muhammad SAW. dari Makkah ke Madinah Tahun 622M - Rufianto, Eric Dwi (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2021)
Background. Member commitment is one of the key variables in determining the success of the organization. The value of members' commitment to the organization becomes a real need for da'wah organizations that carry the mission of preaching Islamic values ​​in an effort to build a good society. This study aims to examine the behavior of Abu Bakr's commitment in the event of the Prophet's migration to Medina in 622M.Aim. Exploring the behavioral form of Abu Bakr's commitment in carrying out the task of accompanying the Prophet when he migrated to Medina. As a reference for da'wah institutions in measuring the commitment of members and the basis for forming organizational commitment to members of their da'wah Methods. The research uses a descriptive qualitative approach and library research.Results. Abu Bakr has implemented organizational commitment behavior that is able to make an important contribution to the journey of the existence and future of Islamic da'wah in the long term. Abu Bakr showed commitment to Islamic organizations in the form of accepting the Hijrah decision set by the Prophet, giving all the resources he had to make the Prophet's migration mission successful to Medina, and having the loyalty to continue to accompany the Prophet in whatever problem conditions/ situations the organization faced until the goal. Organization was achieved. The Prophet arrived safely in Medina.